An Investigation of Merger and Acquisition Performance and Its Determinants - Zhang, Yanhua (2013)
Given the important role of merger and acquisition in the business, this study investigates the performance of merger and acquisition using panel data set of UK manufacturing companies from 2004 to 2008. This study first provides some introductions such as the definition, motives, development of merger and acquisition. Then the study proceeds to review some previous work done by academic researchers. After the literature reviews, the hypotheses proposed in this study are presented and explained in detail. Followed by the hypotheses, the data collection procedures and methodology adopted for investigation are introduced. After that, the study starts to discuss the empirical result and summary the main findings. By using Return on Assets (ROA) as dependent variable in the regression model, the results show that there is no significant difference between merged firms and non-merged firms regarding to their profitability. Furthermore, those determinants of profitability found in the general situation do not exert the same impact on merged firms’ profitability. The result of no significant difference between merged firms and non-merged firm profitability is also robust to the change of profitability indicator. By using return on equity (ROE) as dependent variable, the result again shows that the merger cannot help firms to perform better in profitability. Therefore, the findings of this study suggest that the merger fails to help firms make improvement in terms of profitability.